KONSEP FASIK DALAM AL-QUR’AN PERSPEKTIF AL-IBRIZ: Analisis Teori Sosiologi Karl Mannheim QS. As-Shaf 5-6 - M. Fikriyansyah Ridho; M. Fajrul Munawir (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
Fasiq in the Qur'an refers to behavior that violates Allah's laws and deviates from the truth, often linked to disobedience to divine authority. The Tafsir Al-Ibriz by Bisri Mustofa and Karl Mannheim's sociological theory are used to explore how the concept of fasiq is understood and applied within social and cultural contexts. This study aims to analyze the concept of fasiq in the Qur'an, particularly in Surah As-Saff verses 5-6, through the lens of Tafsir Al-Ibriz and Karl Mannheim's theory. The research is qualitative, focusing on library research. In Islamic teachings, fasiq is a sin, either major or minor, with some views linking it to disbelief depending on the offense. The term fasiq appears 54 times in 23 Surahs of the Qur'an. Surah As-Saff, a Madinan Surah, discusses Sharia law and jihad. Tafsir Al-Ibriz highlights the Jews' rejection and harm towards Prophets Musa and Isa, even though they knew the truth they brought. Mannheim's theory provides insight into the objective meaning of these verses, showing the rejection of the prophets by their people. The expressive meaning is seen in the ongoing harm to Prophet Musa by his people, despite recognizing him as Allah's messenger. Finally, the documentary meaning suggests a hidden indication that in As-Shaf verses 5-6, it is used as reassurance directed to the Prophet Muhammad, encouraging patience when he is harmed by his people.